Inhibin B, AMH, but not INSL3, IGF1 or DHEAS support differentiation between constitutional delay of growth and puberty and hypogonadotropic hypogonadism. (12th August 2015) - Rohayem, J.; Nieschlag, E.; Kliesch, S.; Zitzmann, M.
Summary In pre‐pubertal boys ≥ 14 years, the differentiation between constitutional delay of growth and puberty (CDGP) and hypogonadotropic hypogonadism (HH) is challenging, as current diagnostic tools have limitations in sensitivity and specificity. The aim of this study was to assess the usefulness of markers of gonadal activity, growth axis activation and adrenarche in differentiation between pre‐pubertal CDGP and HH. This retrospective study was carried out between 2006 and 2015 in an academic out‐patient referral centre. The clinical data of 94 boys, aged 13.9–23.2 years and referred for "pubertal delay" were reviewed. Definite diagnoses were established on initial work‐up and clinical follow‐up: 24 boys were diagnosed with HH, 22 boys with CDGP, pre‐pubertal (PP CDGP) at referral and 28 boys with CDGP, early pubertal at referral (EP CDGP), the latter serving as control group. Twenty patients were excluded from evaluation because of previous sex steroid treatment or associated chronic disease. Inhibin B and AMH were measured in all (n = 74); INSL3, IGF1, IGFBP3 and DHEAS in a subset of patients (n = 45) in serum of first presentation. Inhibin B and AMH were higher in boys with PP CDGP than in boys with HH: inhibin B: 87.6 ± 42.5 vs. 19.8 ± 13.9 pg/mL; p < 0.001; AMH: 44.9 ± 27.1 vs. 15.4 ± 8.3 ng/mL; p < 0.001. Receiver operating characteristics (ROC) for the diagnosis of PPCDGP vs. HH (inhibin B ≥ 28.5 pg/mL): sensitivity: 95%, specificity: 75%; AUC: 0.955. In combination with an AMH cut‐off ≥20 ng/mL the specificity increased to 83%. INSL3, IGF1, IGFBP3 and DHEAS levels were not different. In boys with EP CDGP, inhibin B and IGF1 levels were highest (138.7 ± 59.9 pg/mL/289.7 ± 117 ng/mL), whereas AMH levels were lowest (11.7 ± 9.1 ng/mL). Sertoli cell markers are helpful for establishing a prognosis, whether a boy with pubertal delay will enter puberty spontaneously, whereas Leydig cell, growth and adrenal markers are not.